A suggested method for the measurement of world leading research: (illustrated with data on economics) - Andrew J. Oswald (Institute for the Study of Labor (IZA), 2009)
Countries often spend billions on university research. There is growing interest in how to assess whether that money is well spent. Is there an objective way to assess the quality of a nation's world-leading science? I attempt to suggest a method, and illustrate it with modern data on economics. Of 450 genuinely world-leading journal articles, the UK produced 10%, and the rest of Europe slightly more. Interestingly, more than a quarter of these elite UK articles came from outside the best-known university departments. The proposed methodology could be applied to almost any academic discipline or nation.
urn:nbn:de:101:1-20090825526
Keywords: A1; O38; 330; Science; evaluation; European economics; United Kingdom; peer-review; Research Excellence Framework (REF); citations; Research Assessment Exercise (RAE); Publikationsanalyse; Wirtschaftswissenschaft; Wissenschaftliche Methode; Welt; Großbritannien